(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2017)
The paper describes the application of bilingual teaching in German and Serbian in the elementary school "10th October ”in Subotica, the First Nis Gymnasium“ Stevan Sremac ”and the Valjevo Gymnasium. The results of the surveyed teachers and principals show a number of advantages, but also disadvantages in terms of evaluation, teaching materials and support to teachers, as well as continuing bilingual education. The aim of the paper is to point out the current picture and current challenges related to the implementation of teaching in Serbian and German in order to make the approach through the entire bilingual educational process more systematic.